A Criteria- and Case Study-Based Approach to Evaluate Adaptability in Buildings - OZLER Hatice; GUCYETER Basak (Architecture, Civil Engineering, Environment)
Buildings may become functionally obsolete before they reach the end of their service life due to changing social, economic, and technological contexts. A building may undergo one or more transformations during its service life since decreased utility, vacancy, or demolition are not economically, socially, culturally, or environmentally viable options. Buildings with adaptable capacities offer effective solutions for responding to change and creating a sustainable built environment. The present study sought to clarify concepts related to adaptable architecture and develop a criteria-based evaluation approach to assess adaptability parameters in existing buildings. A criteria set was developed based on the literature to define adaptability strategies and parameters and their interconnected spatial, functional, and structural relationships that facilitated change. The magnitude of potential change was weighted and converted to adaptability scores. The adaptability evaluation criteria set was used to assess the adaptability scores of several architectural examples and the findings indicated that the criteria set could be used as both a quantitative and a qualitative evaluation tool.